Targeted Methotrexate Prodrug Conjugated With Heptamethine Cyanine Dye Improving Chemotherapy and Monitoring Itself Activating by Dual-Modal Imaging - Li, Sanpeng; Sun, Zhihong; Meng, Xiaoqing; Deng, Guanjun; Zhang, Jiali; Zhou, Kui; Li, Wenjun; Zhou, Lihua; Gong, Ping; Cai, Lintao (Frontiers in Materials, 2018)
Theranostic prodrug plays a vital role in reducing the side effects and evaluating the therapeutic efficiency of prodrug in vivo. In particular, small conjugate-based theranostic prodrugs have attracted much attention because of their clear and simple structures. In this work, we synthesized a novel tumor-targeting and glutathione-activated conjugate-based theranostic prodrug (Cy-SS-MTX). The prodrug was constructed by conjugating Cy (IR780) to methotrexate (MTX) via a disulphide bond. The Cy dye as targeting molecule bring prodrug to cancer cells and then the prodrug was activated by the high levels of glutathione in tumor. In cell experiments, the results showed the excellent ability of prodrug to target tumor. Meanwhile, the prodrug apparently improved the anti-tumor ability and hugely reduced toxicity of free MTX on normal cells. Furthermore, owing to intramolecular charge transfer between Cy and MTX, the Cy structure in the prodrug showed an absorption peak at 654 nm in UV-Vis spectroscopy. However, when the disulphide bond of prodrug was broken by glutathione, a new UV-Vis absorption peak at 802 nm of Cy structure in prodrug was arised. At the same time, the fluorescence (FL) emission peak at 750 nm (excitation at 640 nm) would turn into 808 nm (excitation at 745 nm). What’s more, the photoacoustic (PA) signal with excitation at 680 and 808 nm also changed. The experimental results in vivo showed that the prodrug has been successfully utilized for real-timely tracking MTX activation by FL and PA imaging upon near infrared laser excitation and cancer targeting therapy. Our studies further encourage application of small conjugate-based prodrug based on tumor-targeted heptamethine cyanine dye as reporter group for targeted therapy and real-timely tracking activation of drug.